2008
DOI: 10.1590/s0103-84782008000100039
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic differences in proembryoid development and green plantlets regeneration through androgenesis in barley varieties

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…In these experiments, the ratio of albino/green plants produced was very high (in particular, for hybrid BG 1-4/98 -79.76%, for genotype BG 367 -100%). Wietholter et al (2008) whereas other researchers (Cistue et al, 2004) also reported 100% ratio of albino/green plants in some barley cultivars [6,7]. On the other hand, in embryogenesis and regeneration frequency there were significant differences between embryoids plated on N6 culture medium and embryoids cultivated on B5 medium.…”
Section: Resultsmentioning
confidence: 91%
“…In these experiments, the ratio of albino/green plants produced was very high (in particular, for hybrid BG 1-4/98 -79.76%, for genotype BG 367 -100%). Wietholter et al (2008) whereas other researchers (Cistue et al, 2004) also reported 100% ratio of albino/green plants in some barley cultivars [6,7]. On the other hand, in embryogenesis and regeneration frequency there were significant differences between embryoids plated on N6 culture medium and embryoids cultivated on B5 medium.…”
Section: Resultsmentioning
confidence: 91%
“…Em cevada, diversas análises genéticas têm mostrado que a regeneração e a indução estão sob controle de diferentes sistemas poligênicos e são influenciadas por genes com efeitos dominantes, em que um alto número de alelos dominantes refletiria em uma alta resposta à cultura (MARCHETTI et al, 1995;WIETHÖLTER et al, 2008) .…”
Section: Resultsunclassified
“…Assim, após uma geração, obtém-se descendentes homozigotos, altamente desejáveis pelos programas de melhoramento. Na cevada, a cultura de anteras é uma das mais eficientes técnicas para obtenção de haplóides e duplo-haplóides e vários estudos sugerem que alguns fatores genéticos parecem estar envolvidos na capacidade de produção de plantas duplo-haplóide (FAROUGHI-WEHR et al, 1982;LARSEN et al, 1991;WIETHÖLTER et al, 2008). Entretanto, mesmo que a capacidade androgenética esteja associada à presença de genes específicos, o sucesso no desenvolvimento dessas plântulas também depende do estádio fisiológico da planta doadora, do pré-tratamento a frio antes da cultura, do estágio do micrósporo, do meio de cultura, da incubação das anteras e do procedimento de regeneração (OLSEN, 1987;MORAES-FERNANDES et al, 1999).…”
unclassified